An Analytical Study on the Legal Protection of Bank Employees from the Perspective of Indonesian Labor Law - Fatwal, Andi Muh.; Miqat, Nurul; Ansar, Ansar (Journal of Law, Politic and Humanities, 2026)
Employee suspension in the banking sector constitutes an administrative measure that creates legal ambiguity within Indonesia’s labor law system, particularly regarding the status of the employment relationship during the suspension period. This condition directly affects employees’ normative rights, including wages, social security, health protection, and employment continuity. In practice, suspension is commonly imposed in cases involving alleged ethical violations, indications of fraud, or the need for internal investigations in accordance with regulations of the Financial Services Authority. This study aims to analyze the legal status of suspended employees under Indonesian labor law and related regulations, as well as to examine the obligations of employers in ensuring fair protection of employees’ rights. This research employs a normative legal method using statutory, conceptual, and case approaches. The findings indicate that suspension does not constitute termination of employment but rather a temporary suspension of work obligations, thereby maintaining the legal employment relationship. Consequently, employees remain entitled to wages and social protection. The absence of specific regulations creates legal gaps that may disadvantage employees. This study recommends the establishment of specific regulations to ensure legal certainty and balanced protection for both parties.